The Effect of Education Costs on Parents' Interest in Registering Children at SDIT Ibu Harapan Bengkalis - Isti Khomah; Haris Riadi (al-Afkar, Journal For Islamic Studies, 2026)
Education is one of the most important aspects of human resource development in a country. In Indonesia, the cost of education is often a determining factor in parents' interest in enrolling their children in certain schools. Many parents feel pressured by the high cost of education, so they are forced to choose schools with lower costs even though the quality may not be as good as the more expensive schools. This study aims to explore more deeply the relationship and the degree of influence between tuition fees and interest. This study applies a quantitative approach with a correlation method that aims to determine the extent to which variables in one or more factors are interconnected. Data was collected by giving questionnaires to 248 student guardians. The results show that tuition fees have no effect on parents' interest in enrolling their children at SDIT Ibu Harapan Bengkalis.